2008
DOI: 10.1111/j.1556-4029.2008.00811.x
|View full text |Cite
|
Sign up to set email alerts
|

Recovery Efficiencies of Anthrax Spores and Ricin from Nonporous or Nonabsorbent and Porous or Absorbent Surfaces by a Variety of Sampling Methods*

Abstract: The 2001 anthrax letter cases brought into focus the need to establish the most effective environmental sampling procedures. Results are presented from two studies aimed at establishing the best procedures for everyday surfaces likely to be contaminated after the release of environmentally stable bioaggressive agents, as exemplified by anthrax spores and ricin. With anthrax spores, contact plates, with mean retrieval rates of 28-54%, performed better than other methods by a wide margin for flat nonporous, nona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
42
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 17 publications
(29 reference statements)
1
42
2
Order By: Relevance
“…As a result, over the last decade needs for quantitative assessment capabilities have driven research on the relative effectiveness of different sampling processes as well as the development of validated surface sampling and sample processing methods (27,49). Notably, the vast majority of these studies have utilized B. anthracis spores (13,20,23,27,28,48) or spores of a surrogate organism (4,5,8,9,18,58). Comparatively little effort has been applied in recent years toward improved surface sampling of viruses (31) and vegetative bacterial cells that represent likely biothreat (BT) agents (or surrogates thereof) (7,29,39,60).…”
mentioning
confidence: 99%
“…As a result, over the last decade needs for quantitative assessment capabilities have driven research on the relative effectiveness of different sampling processes as well as the development of validated surface sampling and sample processing methods (27,49). Notably, the vast majority of these studies have utilized B. anthracis spores (13,20,23,27,28,48) or spores of a surrogate organism (4,5,8,9,18,58). Comparatively little effort has been applied in recent years toward improved surface sampling of viruses (31) and vegetative bacterial cells that represent likely biothreat (BT) agents (or surrogates thereof) (7,29,39,60).…”
mentioning
confidence: 99%
“…A Government Accountability Office (GAO) investigation following the 2001 anthrax incident concluded that validated sampling methods and statistical sampling designs were needed to provide confidence that there is no contamination when all sample results are negative (17, 18). This conclusion strongly reinforces the need for validated sampling methods to effectively respond to biothreats and ensure public safety.Following the 2001 anthrax incident, several research teams developed and investigated (in laboratory studies) the performance of sampling methods using swab, wipe, and vacuum collection devices for Bacillus anthracis or surrogate contaminants on different surfaces (1,2,3,4,5,6,7,13,14,15,16,22,23,25,28,34,38,40,44,45). In addition, the CDC has conducted formal validation studies on two methods for sampling nonporous surfaces: macrofoam swabs (23) and cellulose sponge wipes (39).…”
mentioning
confidence: 99%
“…Preliminary investigations were conducted to select the optimum swab type and the optimum processing method (10,11,16). Others have evaluated the efficiency of various swab types for conducting surface sampling and processing methods for the swabs (1,4,8,15,19). However, using a swab to sample an area larger than 25.8 cm 2 may result in reduced recovery efficiency, so an alternative device for sampling of larger surface areas is needed.…”
mentioning
confidence: 99%